2023
DOI: 10.3390/nu15071743
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Peanut Oligopeptides on Exercise-Induced Fatigue in Mice and Its Underlying Mechanism

Abstract: The aim of this study was to clarify the anti-fatigue effect of peanut oligopeptides (POPs) in mice and to investigate its possible underlying mechanism. A total of 150 male ICR mice were randomly assigned into five groups: control, whey protein (0.50 g/kg·bw), and three peanut peptide groups (0.25, 0.50, and 1.00 g/kg·bw). All the mice were treated with intra-gastric administration for 30 days. Following the intervention, a weight-loaded swimming test, blood lactate concentration, glycogen content, the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…In two clinical studies, curcumin was found to reduce muscle fatigue and soreness after exercise and to reduce, lactic acid accumulation and the level of inflammatory factors, indicating its potential to alleviate sports injuries (Mallard and Briskey, 2021;Bai et al, 2022). Curcumin upregulates Nrf2, PI3K, Akt, AMPK, and mTOR protein expression in fatigued mice, possibly by acting on PI3K/ Akt/AMPK/mTOR and Nrf2 pathways, thus improving oxidative stress and energy metabolism (Chen et al, 2022c;Hu et al, 2023). Resveratrol is a natural polyphenol that exerts antifatigue effects on multiple targets, possibly by acting on core target genes, such as TP53, PIK3R1, AKT1, PIK3CA, and MAPK1 (Ma et al, 2023).…”
Section: Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two clinical studies, curcumin was found to reduce muscle fatigue and soreness after exercise and to reduce, lactic acid accumulation and the level of inflammatory factors, indicating its potential to alleviate sports injuries (Mallard and Briskey, 2021;Bai et al, 2022). Curcumin upregulates Nrf2, PI3K, Akt, AMPK, and mTOR protein expression in fatigued mice, possibly by acting on PI3K/ Akt/AMPK/mTOR and Nrf2 pathways, thus improving oxidative stress and energy metabolism (Chen et al, 2022c;Hu et al, 2023). Resveratrol is a natural polyphenol that exerts antifatigue effects on multiple targets, possibly by acting on core target genes, such as TP53, PIK3R1, AKT1, PIK3CA, and MAPK1 (Ma et al, 2023).…”
Section: Polyphenolsmentioning
confidence: 99%
“…In an analysis of fermented soybean protein ( Fang and Zhang, 2022 ), peptides were found to significantly increase myoglycogen and hepatic glycogen levels, activate p-AMPK/PGC1-α and PI3K/Akt/mTOR signaling pathways, mediate muscle protein synthesis and skeletal muscle hypertrophy, and provide energy to muscle cells, in addition to regulating the gut microbiota; however, it is still unclear what are the exact mechanisms related to the anti-fatigue effects of gut microbes. Intervention with peanut oligopeptides significantly increased the expression of mtTFA and NRF-1 in gastrocnemius mitochondria, suggesting that peanut oligopeptides improve mitochondrial function and promote energy metabolism by reducing damage to mitochondrial membranes due to oxidative stress, resulting in anti-fatigue effects ( Liu et al, 2023 ).…”
Section: Signaling Pathways Affected By Natural Active Ingredients Ag...mentioning
confidence: 99%